Harris Hawks Optimization-Based Algorithm for STATCOM Voltage Regulation of Offshore Wind Farm Grid - Ping-Kui Wang; Yu-Jen Liu; Jun-Tinn Lin; Zen-Wei Wang; Hsu-Chih Cheng; Bo-Xuan Huang; Gary W. Chang (Energies, 2022)
Wind energy is among the fastest-growing electric energy resources worldwide. As the electric power generated by wind turbines (WTs) varies, the WT-connected bus voltage fluctuates. This paper presents a study on implementing a swarm-based proportional and integral (PI) controller for GTO-STATCOM voltage regulator to mitigate the voltage fluctuation caused by the output variations of an offshore wind farm. The proposed swarm-based algorithm for the PI controller is Harris Hawks Optimization (HHO). Simulation results obtained by the HHO algorithm are compared with three other swarm-based algorithms and show that STATCOM with HHO-based PI controller can effectively regulate the WT-connected bus voltage under different wind power output conditions. It shows that the STATCOM compensation performance of the proposed algorithm is superior to that of the compared solutions in maintaining the stable WT-connected bus voltage.